M234. QUALITY OF LIFE IN SCHIZOPHRENIA: THE IMPACT OF RESIDUAL SYMPTOMS AND INTERNALIZED STIGMA. (18th May 2020) - Hofer, Alex; Frajo-Apor, Beatrice; Kemmler, Georg; Pardeller, Silvia; Post, Fabienne
Abstract: Background: Quality of life (QOL) is seen as a key outcome variable in schizophrenia. Factors deemed relevant in this context include the severity of symptoms and internalized Stigma. Methods: Patients with schizophrenia (ICD-10) between the ages of 18 and 65 from outpatient mental health services were included into a cross-sectional study. Apart from the registration of demographic data, various rating scales were used: the Positive and Negative Syndrome Scale (PANSS), the Internalized Stigma of Mental Illness (ISMI) Scale, and the German version of the Lancashire Quality of Life Profile, the Berliner Lebensqualitätsprofil (BELP). Results: 80 patients (47 males, 33 females) with a mean age of 43.0 ± 10.9 years took part in this study. The mean PANSS total score was 71.1 ±25.4, the mean ISMI score was 61.1 ± 14.7 (range: 29–116), and the BELP subscale overall QoL showed a mean score of 4.73 ± 1.17 (range 1–7). Statistical analysis showed a moderate correlation between QoL and internalized stigma (r=-0.468, correlation with general life satisfaction) and a weak correlation with the PANSS total score (r=-0.246, correlation with general life satisfaction). Internalized stigma but not residual symptoms of the disorder negatively predicted QoL Discussion: Our results highlight the complex nature of QoL in individuals suffering from schizophrenia and indicate that outpatients' quality of life correlates moderately with internalized stigma, whereas residual symptoms of the disorder play a secondary role. Accordingly, psychotherapeutic approaches should be applied to reduce internalized stigma, and, ultimately, to improve quality of life.